Medication compliance by cat owners prescribed treatment for home administration - Thomas F. Odom; Christopher B. Riley; Jackie Benschop; Kate E. Hill (Journal of Veterinary Internal Medicine)
Abstract Background Most veterinary literature examining medication compliance has described the phenomenon in dogs. The evidence available regarding factors affecting cat owner medication compliance is limited. Objectives Identify and describe factors associated with cat owners' noncompliance with veterinary recommendations for pet medications, as well as client‐reported barriers and aids to administering medications prescribed by primary care veterinarians. Subjects Cat owners presenting their animals for veterinary examination and treatment. Methods A cross‐sectional survey of cat owners' compliance with veterinary medication recommendations was performed from January 9, 2019, to July 18, 2020. A convenience sample of owners prescribed medication for their pets by veterinarians during or after elective veterinary examination was recruited to respond to questions regarding medication administration experience and compliance. Follow‐up was obtained from owners to determine if the course of medication had been completed. Compliance data were analyzed descriptively, and logistic regression was performed. Results Medication noncompliance was recorded for 39% (26/66) of cat owners. A quarter (16/66) reported challenges in administering medication to their pets; the most commonly cited reason was a resistant pet. Oral administration of antibiotics was significantly associated with noncompliance (P = .01). Clients with limited pet ownership experience were less likely to be noncompliant (P = .04). Conclusions and Clinical Importance Clients' inability to medicate their cats PO may have implications for clinical outcomes and antimicrobial stewardship. Alternatives to direct PO administration of solid‐form medications in cats should be considered. Demonstrating administration techniques to all clients may improve compliance and influence clinical outcome.